Abstinence-reinforcing contingency management improves HIV viral load suppression among HIV-infected people who use drugs: A randomized controlled trial. (1st November 2020) - Cunningham, Chinazo O.; Arnsten, Julia H.; Zhang, Chenshu; Heo, Moonseong; Bachhuber, Marcus A.; Jost, John J.; Grossberg, Robert; Stein, Melissa R.; Sohler, Nancy L.
Highlights: Abstinence-reinforcing contingency management (CM) improved HIV viral load (VL). The mechanism of CM's effect on VL is not completely understood, as CM did not significantly affect abstinence or adherence, but improved VL. CM's median amount was 5.00 and led to improvements in HIV VL. When CM ceased, the improvement in HIV VL diminished. Abstract: Background: HIV-infected people who use drugs (PWUD) have poor HIV outcomes. Few studies tested interventions to improve HIV outcomes among PWUD. Abstinence-reinforcing contingency management (CM) reduces drug use and could also improve HIV outcomes. Methods: From 2012–2017, we conducted a randomized controlled trial testing whether a 16-week abstinence-reinforcing CM intervention improved HIV viral load (VL) among HIV-infected adults using opioids or cocaine. In the CM intervention, drug-free urines led to escalating value of vouchers (2.50-80/voucher, 1320 total maximum). In intention-to-treat mixed-effects linear and logistic regression analyses, we examined whether the CM intervention improved log10 VL (primary outcome), abstinence and antiretroviral adherence (secondary outcomes). Results: Thirty-seven participants were randomized to the CM intervention and 36 to control. Median age was 49.2 years; most were male (61.6%) and non-Hispanic black (46.6%). In CM (vs. control) participants, mean reduction in log10 VL was greater (−0.16 log10 VL copies/mL per 4-week period; 95% CI: −0.29 to −0.03, p < 0.05). Over 16 weeks, CM participants had a mean reduction of 0.64 copies/mL in log10 VL greater than control participants. The CM intervention was not significantly associated with abstinence or adherence. Conclusions: This is the first study to demonstrate improvements in HIV VL via an abstinence-reinforcing CM intervention. Because the CM intervention did not significantly affect abstinence or adherence, the mechanism of its effect is unclear. To end the HIV epidemic, innovative strategies must address individuals with poor HIV outcomes. Abstinence-reinforcing CM may be one potential strategy to improve HIV outcomes among a select group of PWUD.